RASCH MODEL ANALYSIS: DEVELOPMENT OF STUDENTS' NUMERACY LITERACY INTEREST INSTRUMENTS IN MATHEMATICS LEARNING - Dyah Ambarwati; Samsul Maarif (Universitas Bhinneka PGRI, 2025)
The low interest of students in numerical literacy remains a concern, necessitating a specific instrument to measure this aspect. This study aims to develop and validate an instrument for measuring interest in numerical literacy using the Rasch Model. The research subjects consisted of 200 randomly selected high school students in Jakarta. Data were collected through an online questionnaire based on a 5-point Likert scale. The analysis showed that 12 out of 13 items were valid and reliable, with an item reliability value of 0.89 and a Cronbach's Alpha of 0.92. The distribution of item difficulty levels was even, ensuring the instrument could measure students' interest across various ability levels. One item did not fit the validity criteria and needs revision. Additionally, the Rasch Model provided in-depth insights into response consistency and the distribution of item difficulty levels. The developed instrument significantly contributes to measuring interest in numerical literacy, supporting educational decision-making, and designing more effective learning interventions.